Implementasi Pancasila dalam Pendidikan Sekolah Dasar - Dewi Kartini; Dinie Anggraeni Dewi (Universitas Muhammadiyah Enrekang, 2021)
This research was conducted in line with the moral damage that occurred in the community, including students. It can be seen from many cases such as drugs, theft, brawl, sexual crimes, and even murders committed by students in Indonesia. This of course should not be tolerated, it is necessary to make efforts to repair this moral corruption. This research study uses a qualitative method or a descriptive approach. The theory or basis for this discussion is obtained from the results of obtaining information from many sources such as books, journals and articles. This research is used to find ways to reduce or repair moral damage that occurs among students. Then the results show that a lack of moral education is one of the causes of this moral damage. Pancasila as the state ideology and the nation's view of life can certainly be a way to solve this problem, namely by implementing the values of Pancasila in life, the implementation of Pancasila is very important for students including elementary school children to form human quality, good attitudes and behavior to improve the quality of Indonesian education.